Investigating the Effects of Load and Deceleration on Non- Pneumatic Tire Deformation and Stress during Braking - Rahman Wijay; Faizal Adinegoro; Muslim Mahardika; Rachmat Sriwijaya (Global Journals of Research in Engineering, 2023)
The Non-pneumatic tire NPT is a unique tire design that was introduced in 2005 and had the potential to replace traditional tires Unlike conventional tires the NPT uses flexible rods called spokes instead of air to maintain its shape Several spoke models such as kuchwheel Bridgestone and honeycomb models have been developed and tested for static loads using numerical analysis In this study the behavior of the NPT was investigated under braking forces The finite element method FEM was used to calculate load results and the deformation of the NPT was measured with variations in load and deceleration values Results showed that stress and deformation in the NPT increased with higher loads or deceleration values